Verbalisasi Al-Qur’an Melalui Folklor Sebagai Bentuk Pengajaran Islam Pada Masyarakat - Ainur Rhain (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
Verbal art performance of the holy Qur'an embodied in folklores constitutes an effort in performing da’wahs in addition to learning and teaching the values of the Qur'an to the community through an easy-to-understand cultural approach, both in the form of fairy tales, tembang (traditional songs), etc. Some of these folklores constituted the results of the verbalization of the teaching of the Qur'an to the community. The present study traced the roots of the emergence of verbal art performance of the holy Qur'an in the form of folklore, as well as to understand its functions and acceptability in the society. The study employed literature- or library-research approach, since all sources used for this study were in the form of interpretation of books, such as history books, journals and magazines that were related to the topic. Data were analyzed through a qualitative approach involving deductive methods. This study revealed that the verbal art performance of the holy Qur'an was carried out as an effort to do da’wahs and to teach Islamic values to the community at the beginning of Islamic preaching in Indonesia. This was so because not many Indonesians understood the meaning of the holy Qur'an. Hence, the value of the Qur'an would need to be translated into a language that was easily understood by the community; this might be in the form of poetry, encouragement, enlightenment, etc. One form of the verbal art performance of the holy Qur'an included the teaching of "molimo", lir-ilir, etc.